Cacao flower visitation: Low pollen deposition, low fruit set and dominance of herbivores - Vansynghel, Justine; Ocampo Ariza, Carolina; Maas, Bea; Martin, Emily A.; Thomas, Evert; Hanf-Dressler, Tara; Schumacher, Nils-Christian; Ulloque-Samatelo, Carlos; Tscharntke, Teja; Steffan-Dewenter, Ingolf (Wiley, 2022)
Pollination services of cacao are crucial for global chocolate production, yet remain critically understudied, particularly in regions of origin of the species. Notably, uncertainties remain concerning the identity of cacao pollinators, the influence of landscape (forest distance) and management (shade cover) on flower visitation and the role of pollen deposition in limiting fruit set.